2011
DOI: 10.1021/ma102195y
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Nanostructures in Semifluorinated Norbornene Block Copolymers

Abstract: Structure and dynamics of two microphase-separated norbornene block copolymers containing one comb-like component are investigated by X-ray scattering, relaxation spectroscopy as well as differential scanning calorimetry. It is shown that two self-assembling processes on different length scales coexist for these copolymers leading to hierarchically structured systems. Microphase separation of both block copolymer components appears on a scale of 20-25 nm while norbornene main and long semifluorinated side chai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…A similar behavior was also found for chemically different comb-like polymers. [37][38][39]73,74] Notably, for poly(n-alkyl methacrylates), Beiner et al [37] detected two distinct glass transitions: one at lower temperature, associated with the motions of the polyethylene-like side chains (α PE ), and the other (the primary glass transition) at higher temperature, associated with inter-conformational motions of the main chain. This behavior was explained with an intramolecular nanophase separation of incompatible main chains and side chains, by which the sufficiently long alkyl pendant segments self-assembled in distinct nanodomains.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar behavior was also found for chemically different comb-like polymers. [37][38][39]73,74] Notably, for poly(n-alkyl methacrylates), Beiner et al [37] detected two distinct glass transitions: one at lower temperature, associated with the motions of the polyethylene-like side chains (α PE ), and the other (the primary glass transition) at higher temperature, associated with inter-conformational motions of the main chain. This behavior was explained with an intramolecular nanophase separation of incompatible main chains and side chains, by which the sufficiently long alkyl pendant segments self-assembled in distinct nanodomains.…”
Section: Discussionmentioning
confidence: 99%
“…They were previously shown to self‐assemble in prolate single‐chain nanostructures in water solutions . The investigation of the complex hierarchical phase organization of amphiphilic (co)polymers is challenging and in general requires the combination of different techniques . Valuable information can be gained from the study of polymer dynamics at molecular and supramolecular levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 An added benefit of block copolymers is that their chemical composition can be altered to obtain different mechanical properties and morphology without affecting the basic properties of the individual domains. 28,29 In the previous research, a series of paramagnetic polymers based on polyethyleneimine (PEI) were synthesized via quaternization and post-polymerization with FeCl 3 Á 6H 2 O, which indicated that the polymers was difficult to be film due to the nature of polymer electrolyte. 30 In order to obtain magnetic polymer films, a series of block copolymers containing alkyl substituted norbornene derivative and imidazolium chloride based norbornene derivative were prepared via ROMP and post-modification in this research.…”
Section: Introductionmentioning
confidence: 99%
“…Results of molecular dynamics have been reported for sf alkanes [15][16], as well as for various polymers with attached sf chains as side chains either as homopolymers [17][18][19][20] or as copolymers [21][22][23]. The molecular mobility of the chain backbone, as well as that of the sf side chains, ranging from local to segmental motions was followed and related to 28/[282] S. Kripotou et al the structure of the systems.…”
Section: Introductionmentioning
confidence: 99%